EFFECT OF YOGA THERAPY ON LIFE SATISFACTION AMONG GERIATRIC MEN - V. Srinivasa Rao, Dr. S. Murugesan (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Male geriatrics are those who are above 65 and who experience a variety of physiological and cognitive changes as they age. Men are affected by ageing differently than women are, with geriatric men’s morbidity and death being the main emphasis. To make the random group experiment work, 60 older men were asked to take part, 45 were screened, and 30 were chosen at random to be the study’s subjects. This is called random group sampling. The people were split into two groups of fifteen each. The experimental group got yoga therapy for 12 weeks, while the control group did nothing but physical rest. Before and after the training, both the experimental and control groups took a pre-test and a post-test. Scores on Life Satisfaction were recorded. An analysis of variance (ANOVA) was used to find the groups that were significantly different from each other. In the Experimental Group, yogic activities led to Life Satisfaction, according to the study. At a 0.05 level of certainty, this means that the theory is true. What they found was that the yogic techniques helped older men improve Life Satisfaction. KEYWORDS: Yoga therapy practices, Geriatric Men, Life Satisfaction.